A life for a life? : death penalty on trial - Redekop, Vern Neufeld, 1949- (Peace and justice series ;, 1990)
Violent crime touches all of us in some way. We know persons who have been abused, beaten, or killed. We fear theft, rape, murder. We pay taxes to support the police, the judges, and the correctional centers. In this book the author suggests that something is dreadfully wrong with our criminal justice system. It focuses more on punishing the offender than on making things right. It is more concerned with establishing blame than reconciling the victim and offender. "A life for a life' seems to be the motto. If this phrase sounds familiar, it is. But the author claims the Scriptures do not support the principle of revenge. Rather, the Mosaic law provided refuge for the offender and made quick, biased punishment almost impossible.